SORCE‐Based Solar Spectral Irradiance (SSI) Record for Input Into Chemistry‐Climate Studies. Issue 12 (27th December 2019) - Harder, J.W.; Béland, S.; Snow, M.
Abstract: Whole atmosphere chemistry‐climate model (CCM) transient studies require a solar spectral irradiance (SSI) time series with very broad wavelength coverage with an uninterrupted daily cadence over a full solar cycle time period. Herein is described the construction of a SSI record valid over Solar Cycles 23 and 24 (SC23 and SC24) specifically designed to provide: (1) a daily solar spectrum from SORCE (Solar Radiation and Climate Experiment) observations from 208–2400 nm over the 2003 to 2015 time frame, (2) a wavelength extension of this spectrum out to 10000 nm from daily spectral synthesis from the Solar Radiation Physical Model (SRPM), (3) SRPM gap‐filled spectra during the extended SORCE safe‐hold time period (Aug 2013–March 2014) and back to Solar Cycle 23 maximum conditions in 2001 and 2002, (4) analysis of solar images generated by the Precision Solar Photometric Telescope (PSPT) network from the Mauna Loa Solar Observatory (MLSO) and Rome Observatory (OAR) (These images act both as input to the SRPM model and as a stand‐alone proxy of solar variability.), (5) documentation of uncertainties and biases in the time series as a function of wavelength, and (6) comparative analysis of the SORCE time series with SRPM over the full wavelength range of the data set. Plain Language Summary: The Sun delivers about 10, 000 times more energy to the Earth climate system than any other source of energy. In spite of its overwhelming dominance in energy delivery, the Sun exerts a very benevolent influence on our climate compared to how other observable stars might behave. Nonetheless, the Sun is still a variable star, and its subtle variability is an important ingredient to understanding the evolution of the Earth climate system. For Earth chemistry‐climate models to discriminate between natural and anthropogenic contributions to climate change, a high‐quality data record of the variability of the Sun is needed both on a daily basis and over a full 11‐year solar cycle. The construction of such a record requires a unification of available observations of the radiant power of the Sun and a solar physics model to fill in where our observation systems are lacking. We describe here a way of producing such a data record for the Earth science community. Key Points: Construct a broad wavelength coverage solar spectrum for input to chemistry‐climate models and document its creation and uncertainties Missing observational irradiance data are filled with spectral synthesis data from the Solar Radiation Physical Model (SRPM) Employs solar image acquisition and processing for SRPM synthesis and as a stand‐alone proxy of solar variability